Immature defense mechanisms mediate the relationship between negative life events and depressive symptoms - Ma, Dandan; Cao, Jinya; Wei, Jing; Jiang, Jing (Frontiers in Psychiatry, 2024)
Objective This study aimed to analyze the patterns of life events (LEs) and defense mechanisms in outpatients with depression and investigate the mediating role of defense mechanisms in the association between LEs and depressive symptoms in a psychosomatic outpatient sample in China. Materials and methods All of 2,747 outpatients (aged 18–65) from psychosomatic department were investigated in this study. LEs, depressive symptoms, and defense mechanisms were assessed by the Life Events Scale (LES), Patient-Health-Questionnaire-9 (PHQ-9), and the Defense Style Questionnaire (DSQ), respectively. Results Based on the optimal cut-off point of PHQ-9, 1840 (67.0%) patients had a PHQ-9 score of 10 or higher (depression group), and 907 (33.0%) had a score below 10 (non-depression group). The scores of Negative Life Events (NLEs), immature and intermediate defense mechanisms in the depression group were significantly higher than those in the non-depression group, while the scores of mature defense mechanisms were the opposite (p < 0.001). NLEs was directly related to depressive symptoms (b = 0.010, p < 0.001), and significant indirect effect via immature defense mechanisms (b = 0.008, p < 0.001) was observed. Conclusion Immature defense mechanisms play an important mediating role in the relationship between NLEs and depressive symptoms. Helping patients improving defense mechanisms and dealing with NLEs may be of great help in the treatment of relevant patients.